Physical and oxidative stability of functional avocado oil high internal phase emulsions collaborative formulated using citrus nanofibers and tannic acid. (September 2018) - Wang, Jia-Shui; Wang, An-Bang; Zang, Xiao-Ping; Tan, Lin; Ge, Yu; Lin, Xing-E.; Xu, Bi-Yu; Jin, Zhi-Qiang; Ma, Wei-Hong
Abstract: Avocado oil-based high internal phase emulsions (HIPEs) were formed and stabilized at by citrus nanofibers (CNFs) and tannic acid (TA) via a simple shear-induced emulsification technique. CNFs/TA colloidal complex (CTNFs) based on the hydrogen-bonding interaction between citrus nanofibers and TA was successfully generated. These complex colloidal nanofibers with enhanced interfacial reactivity can be utilized for the preparation of stable avocado oil-based HIPEs by one-step homogenization. A dense and orderly interfacial architecture via the combination of steric hindrance from fibers membrane and interfacial cargo of TA endowed the emulsions with favorable oxidative stability, evidenced by low lipid hydroperoxides, malondialdehyde and hexanal levels in the emulsions after thermally accelerated storage. The HIPEs are formed as a gel with a texture that can be modulated by adjusting TA concentration. Furthermore, a pH triggered responsible propertie was observed as a result of the pH-dependent bond of TA and citrus nanofibers. These results will likely extend the use of these surfactant-free, and potentially edible emulsions to new food, cosmetic, and pharmaceutical applications. Graphical abstract: Image Highlights: Surface of citrus nanofiber was modified with tannic acid via hydrogen bonding. Avocado oil-based high internal phase emulsions (HIPEs) are successfully constructed. HIPEs exhibit excellent physical stability and oxidative stability. pH-Responsible behavior of avocado oil-based HIPEs.